Revisiting the dimensions and determinants of women’s empowerment, and links to household food security in rural farming communities of Bangladesh - Haque, Sadika; Salman, Mohammed; Hoque, M. Nazmul; Sarker, Abdur Rouf (Bangladesh Agricultural University, 2023)
Women’s empowerment and food security are critical issues in Bangladesh, particularly in rural farm households where women face several challenges that impede their empowerment and household food security. Therefore, this study aimed to assess the degree of women’s empowerment (WE), investigate its determinants, measure household food security, and uncover the links between WE and household food security in rural farming communities of Bangladesh. The study collected primary data (350 households) using a random sampling technique and analyzed it using statistical methods such as the pro-WEAI index, Household Food Insecurity Access Scale (HFIAS), Poisson regression, and Partial Least Square Structural Equation Model (PLS-SEM). The study revealed that less than 1% of women in rural farm households in Bangladesh were empowered, and only 18% of households were food secure. Women’s years of schooling, household size, farm types, and the presence of migrated members in households were positively associated with women’s empowerment, while the distance of farms from households was negatively associated. The PLS-SEM showed that access to decisions on financial services, input in productive decisions (farm), and ownership of assets were negatively associated with household food insecurity, while mobility was positively associated. Furthermore, the study revealed that work balance, respect among household members, and attitude about intimate partner violence were negatively associated with household food insecurity. In conclusion, the study highlights the need for developing a gender-inclusive food system governance and revised food policy to empower rural women and improve household food security in Bangladesh.